2021
DOI: 10.1128/jcm.01110-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanopore Sequencing as a Diagnostic Tool for the Rapid Identification of Mycoplasma bovis from Individual and Pooled Respiratory Tract Samples

Abstract: Rapid identification of Mycoplasma bovis infections in cattle is a key factor to guide antimicrobial therapy and biosecurity measures. Recently, nanopore sequencing became an affordable diagnostic tool for both clinically relevant viruses and bacteria, but the diagnostic accuracy for M. bovis identification is undocumented. Therefore, in this study nanopore sequencing was compared to rapid identification of M. bovis with MALDI-TOF MS (RIMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…A recent investigation by Bokma et al . using a Bayesian latent class model described a lower sensitivity for identification of M. bovis with nanopore sequencing (77.3% [95% credible interval, 57.8 to 92.8%]) as compared to the described method of rapid identification of M. bovis by MALDI-TOF MS [RIMM] (93.0% [76.8 to 99.5%]) [ 70 ]. The investigation by Bokma et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation by Bokma et al . using a Bayesian latent class model described a lower sensitivity for identification of M. bovis with nanopore sequencing (77.3% [95% credible interval, 57.8 to 92.8%]) as compared to the described method of rapid identification of M. bovis by MALDI-TOF MS [RIMM] (93.0% [76.8 to 99.5%]) [ 70 ]. The investigation by Bokma et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies using NGS techniques have shown the complex microbial composition and found the common bacterial pathogens for BRD in the lungs of both healthy and sick cattle [ 1 , 16 , 23 , 43 , 52 ]. With the improvement of techniques, nanopore sequencing and multiple omics [i.e., metagenomics (the study of a collection of genomes and genes from the members of a microbiota by shotgun sequencing), metaproteomics, metatranscriptomics and metabolomics] are becoming more effective to investigate the composition and functions of the respiratory microbiome [ 59 , 60 ]. In cattle, the bacterial community and BRD-associated pathogens were found when using metagenomics to measure all the genes of all the microbes in an environment [ 20 , 25 , 61 63 ], but still no reports using other omics were found.…”
Section: Techniques Used In the Studies Of The Respiratory Microbiomementioning
confidence: 99%
“…However, to the authors' knowledge, there are no peer-reviewed Bayesian latent class evaluations of PCR tests for NCD pathogens available. Previous work on PCR for bovine respiratory disease pathogens has shown that these tests do not have a perfect sensitivity and specificity (Bokma et al, 2021).…”
Section: Etiology and Diagnosticsmentioning
confidence: 99%
“…The viral metagenome can be identified in a sample, as well as certain bacteria. The technique has already shown its added value for diagnostics in diarrheic pigs and bovine respiratory disease (Theuns et al, 2018;Bokma et al, 2021). Other techniques like immunofluorescence assay or the carbolfuchsine smear method for microscopic examination for C. parvum are either not feasible on farm level or no longer widely offered by veterinary laboratories, and hence outside the scope of this review.…”
Section: Etiology and Diagnosticsmentioning
confidence: 99%